2013
DOI: 10.1177/1087057113476551
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Throughput Fluorescence Polarization DNA Cleavage Assay for the Identification of FEN1 Inhibitors

Abstract: Flap endonuclease-1 (FEN1) is a highly conserved metallonuclease and is the main human flap endonuclease involved in the recognition and cleavage of single-stranded 5′ overhangs from DNA flap structures. The involvement of FEN1 in multiple DNA metabolism pathways and the identification of FEN1 overexpression in a variety of cancers has led to interest in FEN1 as an oncology target. In this article, we describe the development of a 1536-well high-throughput screening assay based on the change in fluorescence po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Several attempts to develop FEN1 inhibitors have been described (Tumey et al, 2004, Tumey et al, 2005, Mcwhirter et al, 2013, Wadhwa and Jadhav, 2015, Dorjsuren et al, 2011). Tumey et al reported that N-hydroxy urea derivatives are FEN1 inhibitors, and compound #20 has an impressive IC50 value of 3 nM (Tumey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to develop FEN1 inhibitors have been described (Tumey et al, 2004, Tumey et al, 2005, Mcwhirter et al, 2013, Wadhwa and Jadhav, 2015, Dorjsuren et al, 2011). Tumey et al reported that N-hydroxy urea derivatives are FEN1 inhibitors, and compound #20 has an impressive IC50 value of 3 nM (Tumey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of highthroughput, robust screening techniques have successfully identified potential novel inhibitors of DNA repair proteins to be taken forward. 99,100 The studies discussed here thus far suggest that targeting DNA repair endonucleases in combination with DNA-damaging agents may be a promising anticancer strategy.…”
Section: Dna Repair Endonucleases As Targets For Cancer Therapymentioning
confidence: 99%
“…In 2013, AstraZeneca (London, UK) conducted a high-throughput screen of 850,000 compounds using a fluorescent DNA cleavage assay to determine FEN1 inhibition activity. 99 This screen resulted in the identification of 6261 compounds with FEN1 inhibition activity at an IC 50 of less than 100 µM. 99 A study in colorectal cancer cell lines revealed that FEN1 inhibition by a number of small molecules had a synthetically lethal effect in cells deficient in the ubiquitin ligase CDC4.…”
Section: Fen1 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized annotation of in-house HTS assays using BAO is demonstrated by previously published in-house screening assay development experiments ( Table 1). [10][11][12] The assay design and detection methods of the in-house HTS assays have been analyzed together with 233 primary PubChem HTS assays. 7 Annotated PubChem assays have been provided by the BAO team and are mainly biochemical assays, G protein-coupled receptor (GPCR) assays, and various assays detected by luminescence.…”
Section: Assay Annotationmentioning
confidence: 99%